Bombay cinema : an archive of the city - Mazumdar, Ranjani (Permananent black, 2007)
In this analysis, Mazumdar reveals a complex postnationalist world, convulsed by the social crisis of the 1970s and transformed by the experience of globalization in the 1990s.